2017
DOI: 10.1371/journal.pone.0190229
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A5 reduces early plaque formation in ApoE -/- mice

Abstract: Annexin A5 (AnxA5) exerts anti-inflammatory, anticoagulant and anti-apoptotic effects through its binding to cell surface expressed phosphatidylserine. We previously showed that AnxA5 can stabilize advanced atherosclerotic plaques by reducing macrophage infiltration. We now investigated the effects of AnxA5 administration on the onset of atherosclerosis development. Eight-week-old ApoE-/-mice were fed a western diet while being administered AnxA5 or control (M1234) for a total of 6 weeks. AnxA5 administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…In apoE −/− mice fed a western style diet, subsequent AnxA5 administration reduced recruitment and activation of monocytes to the inflamed lesion site, thereby reducing plaque inflammation [ 256 ]. Moreover, when AnxA5 was administered simultaneously with the western style diet, reduced apoptotic rates contributed to the significantly reduced plaque size [ 257 ]. Using hypercholesterolemic ApoE*3 Leiden mice as a model for MI-reperfusion injury, AnxA5 treatment strongly reduced infarct size and improved cardiac function, most likely via the attenuation of the post-ischaemic inflammatory response [ 258 ].…”
Section: Anxa5mentioning
confidence: 99%
“…In apoE −/− mice fed a western style diet, subsequent AnxA5 administration reduced recruitment and activation of monocytes to the inflamed lesion site, thereby reducing plaque inflammation [ 256 ]. Moreover, when AnxA5 was administered simultaneously with the western style diet, reduced apoptotic rates contributed to the significantly reduced plaque size [ 257 ]. Using hypercholesterolemic ApoE*3 Leiden mice as a model for MI-reperfusion injury, AnxA5 treatment strongly reduced infarct size and improved cardiac function, most likely via the attenuation of the post-ischaemic inflammatory response [ 258 ].…”
Section: Anxa5mentioning
confidence: 99%
“…5 , 6 , S1). Stoer et al [ 27 ] and Burgmayer et al [ 26 ] demonstrated that anxA5 treatment reduced the amount of macrophages in different stages of plaque development, but attenuated plaque size and the amount of apoptotic cells only in early stages. The adventitia—the outer layer of the vessel wall—is a collagen-rich extracellular matrix with bunches of fibroblasts, perivascular nerves, and microvessels.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its diagnostic and therapeutic potential in the important field of viral infection, anxA5 has shown promising therapeutic effects in several other areas as well. For cardiovascular disease, anxA5 was reported to reduce inflammation in advanced atherosclerotic plaques and to attenuate plaque progression in early disease [ 26 , 27 ]. Furthermore, anxA5 reduced vessel inflammation and atherosclerosis after arterial cuff placement or vein graft surgery [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cell adhesion assay was performed as described previously 25 . HUVECs were seeded to confluence in 6-well plates and then stimulated by LPS (0.2 μg/ml, Sigma) for 6 h. Then activated HUVECs were untreated or treated with ANXA5/A5m (250 nM) for 30 min in complete medium supplemented with 2.5 mM Ca 2+ , and labeled with Hoechst (Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…In vivo ANXA5 dampens inflammation when administered to various mouse models 8 , 22 – 24 . Administration of ANXA5 reduces inflammation and suppresses plaque development in a PS-dependent manner 25 .…”
Section: Introductionmentioning
confidence: 99%